Rethinking Sustainable Development in the Age of Artificial Intelligence - De Falco, Ciro Clemente (Italian Sociological Review, 2024)
Today, artificial intelligence is being applied in areas ranging from public institutions to people’s everyday lives. Its pervasiveness makes it a protagonist of essential changes in society. In recent years, sustainable development has moved to the centre of public discourse and national and international planning. The UN defines sustainability as “meeting the needs of the present without compromising the ability of future generations to meet their own needs” and has developed the 2030 Agenda to achieve this objective (UN, 2015). AI’s ubiquity and relevance mean it can be either a facilitator or a barrier to sustainable development. In a paper published in Nature, Vinuesa and colleagues (2020) highlighted how AI can facilitate the achievement of Sustainable Development Goals but also pose a threat to their attainment. The importance of AI today requires a redefinition of the concept of sustainable development in order to protect areas that have become particularly sensitive to its proliferation. Therefore, reflection on how AI can contribute to achieving sustainable development should be in parallel with how AI redefines the dimensions of sustainable development. The dimensions worthy of attention identified in this work are Transparency, Autonomy, Democracy and Privacy.